Traditional use, chemical constituents, and pharmacological activity of Maytenus laevis Reissek - Ascate-Pasos, Manuel Eduardo; Ganoza-Yupanqui, Mayar Luis; Suárez-Rebaza, Luz Angélica; León-Vargas, Frank Romel; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2022)
Background: Species of the genus Maytenus are recognized for their uses in pain and cancer-related conditions. The purpose of the literature review was to compile scientific information on the traditional uses, chemical constituents, and pharmacological activities of Maytenus laevis Reissek. Methods: The scientific name Maytenus laevis and its synonyms, in combination with "traditional uses" OR ethnobotany OR "chemical constituents" OR "chemical composition" OR phytochemistry OR "biological activities" OR "pharmacological activities" OR pharmacology, were searched in the main databases. Seventy papers were selected according to research type and relevance. Results: M. laevis is known by the common name ''chuchuhuasi'' and is traditionally used for the treatment of rheumatism and cancer, although it is also used as a sexual enhancer. Its chemical constituents are pyridine-derived alkaloids, triterpenes, sterols, iridoids and phenolic compounds, and are of great pharmacological interest, but only anti-inflammatory, antibacterial, antiparasitic and anticancer activities have been proven in preclinical studies. In addition, different studies point to its growth in Peru, due to it being confused with other species of the genus Maytenus. Conclusions: Reports on its chemical composition indicate the therapeutic potential of this species. However, there is little information on its pharmacological effects at the preclinical and clinical levels. Therefore, further research could verify its correct distribution and scientific validation of its traditional uses. In addition, specific chemical markers could be used to differentiate it from other species. Keywords: Maytenus laevis, Maytenus javensis, Monteverdia laevis, traditional use, chemical constituents, pharmacological activities.